Genetic variation spectrum in ATP7B gene identified in Latvian patients with Wilson disease. Issue 4 (7th June 2017) - Zarina, Agnese; Tolmane, Ieva; Kreile, Madara; Chernushenko, Aleksandrs; Cernevska, Gunta; Pukite, Ieva; Micule, Ieva; Krumina, Zita; Krumina, Astrida; Rozentale, Baiba; Piekuse, Linda
Abstract: Background: Wilson disease (WD) is an autosomal recessive disorder of copper metabolism caused by allelic variants in ATP7B gene. More than 500 distinct variants have been reported, the most common WD causing allelic variant in the patients from Central, Eastern, and Northern Europe is H1069Q. Methods: All Latvian patients with clinically confirmed WD were screened for the most common mutation p.H1069Q by PCR Bi‐PASA method. Direct DNA sequencing of gene ATP7B (all 21 exons) was performed for the patients with WD symptoms, being either heterozygous for H1069Q or without it on any allele. Results: We identified 15 different allelic variants along with eight non‐disease‐causing allelic variants. Based on the gene molecular analysis and patients' clinical data variant p.His1069Gln was found in 66.9% of WD alleles. Wide clinical variability was observed among individuals with the same ATP7B genotype. The results of our study confirm that neurological manifestations of WD are typically present later than the liver disease but no significant association between the presence/absence of the most common genetic variant and mode of initial WD presentation or age at presentation was identified. Conclusions: (1) The most prevalent mutation in Latvian patients with Wilson disease was c.3207C>A (p.His1069Gln); (2) No significant phenotype–genotype correlation was found in Latvian patients with Wilson disease; (3) The estimated prevalence of Wilson disease in Latvia is 1 of 24, 000 cases which is higher than frequently quoted prevalence of 1: 30, 000. Abstract : In this paper, we report on the latest discoveries in analyzing mutations in gene ATP7B in Wilson disease patients in Latvia. This is significant because the article represents genetic structure of Latvian patients with Wilson disease, including two undescribed and other rare genetic variants of ATP7B gene, as well as shows frequency of Wilson disease in Latvia, which is very high in comparison to other populations.